Técnicas de adaptación no farmacológicas usadas en odontopediatría para disminuir la ansiedad durante la consulta odontológica. Revisión de la literatura (2020)
There are different techniques to minimize anxiety levels and help in managing behavior, which allow pediatric patients to feel less anxious in the consultation, improve their behavior and increase the regularity of scheduled visits to the dentist. OBJECTIVE: To determine non-pharmacological adaptation techniques, such as behavioral modeling techniques in dental care programs. Through a bibliographic review. MATERIALS AND METHODS: Descriptive research, only 53 articles were approved and reviewed, each one is divided as follows: 19 articles on dental anxiety, 5 articles on techniques to reduce pain and anxiety in pediatric dentistry 4 articles that record and they compare the scales used to measure dental anxiety: 4 articles from clinical studies, 6 articles that deal with a literature review of non-pharmacological techniques used in pediatric dentistry and 15 articles on music therapy, aromatherapy and audiovisual distraction for the management of anxiety. . RESULTS: The main non-pharmacological adaptation techniques were: audiovisual distraction with 45%, followed by the music therapy technique with 34%, then aromatherapy with a value of 17% and 4% for other techniques found. CONCLUSIONS: The video distraction technique and the Venham test were the most widely implemented according to the literature, achieving, respectively, to decrease and evaluate anxiety levels in pediatric patients in a more accurate way. KEY WORDS: Anxiety, aromatherapy, pediatric dentistry, musictherapy, distraction.